Heterogeneous Changes in Western North American Glaciers Linked to Decadal Variability in Zonal Wind Strength. Issue 1 (15th January 2019) - Menounos, B.; Hugonnet, R.; Shean, D.; Gardner, A.; Howat, I.; Berthier, E.; Pelto, B.; Tennant, C.; Shea, J.; Noh, Myoung‐Jong; Brun, F.; Dehecq, A.
Abstract: Western North American (WNA) glaciers outside of Alaska cover 14, 384 km 2 of mountainous terrain. No comprehensive analysis of recent mass change exists for this region. We generated over 15, 000 multisensor digital elevation models from spaceborne optical imagery to provide an assessment of mass change for WNA over the period 2000–2018. These glaciers lost 117 ± 42 gigatons (Gt) of mass, which accounts for up to 0.32 ± 0.11 mm of sea level rise over the full period of study. We observe a fourfold increase in mass loss rates between 2000–2009 [−2.9 ± 3.1 Gt yr −1 ] and 2009–2018 [−12.3 ± 4.6 Gt yr −1 ], and we attribute this change to a shift in regional meteorological conditions driven by the location and strength of upper level zonal wind. Our results document decadal‐scale climate variability over WNA that will likely modulate glacier mass change in the future. Plain Language Summary: Glaciers in western North America provide important thermal and flow buffering to streams when seasonal snowpack is depleted. We used spaceborne optical satellite imagery to produce thousands of digital elevation models to assess recent mass loss for glaciers in western North America outside of Alaska. Our analysis shows that glacier loss over the period 2009–2018 increased fourfold relative to the period 2000–2009. This mass change over the last 18 years is partly explained by changes in atmospheric circulation. Our results can be used for future modeling studies to understand the fate of glaciers under future climate change scenarios. Key Points: We provide a comprehensive assessment of mass change for western North American (WNA) glaciers excluding those in Alaska WNA glaciers lost 117 +/‐ 42 gigatons (Gt) of mass over the period 2000‐2018 and could account for 0.32 +/‐ 0.11 mm of sea level rise Regional changes in glacier mass are partly explained by decadal scale changes in atmospheric circulation